Kalejdoskopski pogled na umetno inteligenco in pravo človekovih pravic - Sancin, Vasilka (Podjetje in delo, 2023)
This article highlights, through the prism of the Universal Declaration of Human Rights, some of the issues raised by the development and use of artificial intelligence (AI) for the realisation of fundamental human rights, which should be taken into account both in the AI design and in its subsequent operationalisation. AI brings many benefits to humanity, but also serious risks. That is why a kaleidoscopic view has been chosen for the purposes of this discussion, as virtually every moment, AI presents new opportunities and pitfalls. It is particularly important that the human rights perspective is duly taken into account throughout the life cycle of AI, and that human rights law experts are appropriately involved in the human rights impact assessment of AI.
Keywords: Človekove pravice; nadzor; regulacija; Splošna deklaracija človekovih pravic; Umetna inteligenca